2011
DOI: 10.1186/1476-069x-10-32
|View full text |Cite
|
Sign up to set email alerts
|

Individual exposures to drinking water trihalomethanes, low birth weight and small for gestational age risk: a prospective Kaunas cohort study

Abstract: BackgroundEvidence for an association between exposure during pregnancy to trihalomethanes (THMs) in drinking water and impaired fetal growth is still inconsistent and inconclusive, in particular, for various exposure routes. We examined the relationship of individual exposures to THMs in drinking water on low birth weight (LBW), small for gestational age (SGA), and birth weight (BW) in singleton births.MethodsWe conducted a cohort study of 4,161 pregnant women in Kaunas (Lithuania), using individual informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 38 publications
3
57
2
Order By: Relevance
“…A separate model was built in each country (region in the case of Spain) for total trihalomethanes, chloroform, and total brominated trihalomethanes following similar methods as discussed in study-specific published papers. [8][9][10]17,18 Linear regression and generalized additive models were fitted using geographical and temporal variables (month, year). Among models retaining significant variables (p value<0.05), criteria to select the final model included the adjusted R-squared and the Akaike Information Criteria.…”
Section: Exposure Assessment For Water Contaminantsmentioning
confidence: 99%
See 1 more Smart Citation
“…A separate model was built in each country (region in the case of Spain) for total trihalomethanes, chloroform, and total brominated trihalomethanes following similar methods as discussed in study-specific published papers. [8][9][10]17,18 Linear regression and generalized additive models were fitted using geographical and temporal variables (month, year). Among models retaining significant variables (p value<0.05), criteria to select the final model included the adjusted R-squared and the Akaike Information Criteria.…”
Section: Exposure Assessment For Water Contaminantsmentioning
confidence: 99%
“…15,16 Analyses of the association of trihalomethanes with birth outcomes for country-specific populations included in HiWate (Health Impacts of Long-Term Exposure to Disinfection By-Products in Drinking Water) have been published previously. 8,9,10,17,18 …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, when individual values are analyzed, all samples presented concentrations of BDCM and TBM above zero, which is the maximum contaminant level goal for these two compounds. High THMs values usually occur at points in the distribution system with the longest residence time or water age, such as reservoirs, oversized pipes and network dead ends [9]. Figure 2 presents the mean results of samples grouped by five main geographical areas.…”
Section: Resultsmentioning
confidence: 99%
“…In 2011, Regina Grazuleviciene et al found epidemiological evidence for a dose-response relationship between the THMs blood internal dose of pregnant women, exposed through drinking water by ingestion, showering and bathing, and child low birth weight found epidemiological evidence for a dose-response relationship between THM internal dose exposure and low birth weight [9]. Identical conclusions were achieved by Iszatt N. et al in 2014 suggesting that a high decrease in chloroform concentrations in tap water is associated with a statistically significant reduction in very low birth weight rates [10].…”
Section: Introductionmentioning
confidence: 99%
“…Seeking to improve the exposure assessment, studies have begun to incorporate behavioural determinants of different routes of exposure to DBPs such as dermal absorption and inhalation during bathing and showering, and ingestion of drinking water (Savitz et al 2006;Hoffman et al, 2008;MacLehose et al, 2008). In our previous prospective Kaunas cohort study, which incorporated of different routes of exposure to THMs, we found doseresponse relationships for entire pregnancy and trimester-specific gestational THMs and chloroform internal dose for low birth weight and reduction in birth weight (Grazuleviciene et al, 2011). The epidemiological studies concluded that, while there appears to be suggestive evidence associating elevated total THM levels with some adverse reproductive outcomes, evidence for relationships with preterm birth and fetal growth is inconclusive and inconsistent (Richardson et al, 2003;Lewis et al, 2006;Grellier et al, 2010).…”
Section: Introductionmentioning
confidence: 99%